Pharmacological blockade of aquaporin-1 water channel by AqB013 restricts migration and invasiveness of colon cancer cells and prevents endothelial tube formation in vitro. Issue 1 (December 2016) - Dorward, Hilary; Du, Alice; Bruhn, Maressa; Wrin, Joseph; Pei, Jinxin; Evdokiou, Andreas; Price, Timothy; Yool, Andrea; Hardingham, Jennifer
Abstract Background Aquaporins (AQP) are water channel proteins that enable fluid fluxes across cell membranes, important for homeostasis of the tissue environment and for cell migration. AQP1 knockout mouse models of human cancers showed marked inhibition of tumor-induced angiogenesis, and in pre-clinical studies of colon adenocarcinomas, forced over-expression of AQP1 was shown to increase angiogenesis, invasion and metastasis. We have synthesized small molecule antagonists of AQP1. Our hypothesis is that inhibition of AQP1 will reduce migration and invasiveness of colon cancer cells, and the migration and tube-forming capacity of endothelial cellsin vitro . Methods Expression of AQP1 in cell lines was assessed by quantitative (q) PCR, western blot and immunofluorescence, while expression of AQP1 in human colon tumour tissue was assessed by immunohistochemistry. The effect of varying concentrations of the AQP1 inhibitor AqB013 was tested on human colon cancer cell lines expressing high versus low levels of AQP1, using wound closure (migration) assays, matrigel invasion assays, and proliferation assays. The effect of AqB013 on angiogenesis was tested using an endothelial cell tube-formation assay. Results HT29 colon cancer cells with high AQP1 levels showed significant inhibition of migration compared to vehicle control of 27.9 % ± 2.6 % (p < 0.0001) and 41.2 % ± 2.7 (p <0.0001) treated with 160 or 320 μM AqB013 respectively, whereas there was no effect on migration of HCT-116 cells with low AQP1 expression. In an invasion assay, HT29 cells treated with 160 μM of AqB013, showed a 60.3 % ± 8.5 % decrease in invasion at 144 hours (p < 0.0001) and significantly decreased rate of invasion compared with the vehicle control (F-test, p = 0.001). Almost complete inhibition of endothelial tube formation (angiogenesis assay) was achieved at 80 μM AqB013 compared to vehicle control (p < 0.0001). Conclusion These data provide good evidence for further testing of the inhibitor as a therapeutic agent in colon cancer.